THE EFFECT OF LEADERSHIP STYLE, WORK ENVIRONMENT, WORK MOTIVATION AND JOB SATISFACTION ON THE PERFORMANCE OF PAUH CAMAT OFFICE EMPLOYEES PADANG CITY - Yass Andria; Muliardi Muliardi; Afridon Afridon; Marsen Marsen (SEAN Institute, 2022)
This study aims to see the effect of (1) Leadership Style on the performance of the Pauh Sub-District Office of Padang City. (2) The work environment on the performance of the Pauh Sub-District Office of Padang City. (3) Work motivation on the performance of the Pauh Sub-District Office employees, Padang City. (4) Job satisfaction on the performance of the Pauh Sub-District Office of Padang City (5) Job satisfaction, work environment, work motivation and job satisfaction have a combined effect on the performance of the Pauh Sub-District Office of Padang City. The population in this study is all there are 70 employees of the Pauh Subdistrict Office of Padang City. Techniques for determining the number of samples taken as respondents with this technique in sampling using the total sampling technique (whole sample). Total sampling is a sampling technique where the number of samples is the same as the population (Sugiyono, 2017). The reason for taking total sampling is because according to (Sugiyono, 2017) the total population is less than 100, and the entire population is used as a research sample. This study shows that (1) Leadership styleprovide a positive influence on the performance of the Pauh District Office of Padang City employees. (2) Work environment provides a positive influence on the performance of the Pauh District Office of Padang City employees. (3) Work motivation provides a positive influence on the performance of the Pauh District Office of Padang City employees. (4) Job satisfaction provides a positive influence on the performance of the Pauh District Office of Padang City (5) Leadership style, work environment, work motivation, and job satisfaction jointly have a positive effect on the performance of the Pauh District Office employees of Padang City.